Nanomechanics of Refractory Transition‐Metal Carbides: A Path to Discovering Plasticity in Hard Ceramics. Issue 8 (18th June 2015) - Kiani, Sara; Yang, Jenn‐Ming; Kodambaka, Suneel; Green, D. J.
<x xml:space="preserve">Abstract</x> Refractory carbides of transition metals (Zr, Ta, etc.), owing to a mixture of ionic, covalent, and metallic bonding, exhibit high hardness (10s of GPa), high elastic moduli (100s of GPa), good resistance to wear, ablation, and corrosion, high‐temperature mechanical strength, along with good electrical conductivities. They are attractive as high‐temperature structural components in aerospace vehicles. Although these materials are exceptionally hard, their structural applications at low temperatures have been limited because of their brittleness. The design of ceramic materials possessing both high hardness and enhanced ductility has been a long‐standing challenge. Various research studies have focused on this topic with limited success. Here, we present a brief review of our recent results obtained from direct observations of mechanical deformation during uniaxial compression of group IV and group V transition‐metal carbide (ZrC and TaC) single crystals inside a transmission electron microscope. Our studies provide new insights into the mechanical deformation mechanisms and help to identify strategies for enhancing room‐temperature plasticity in this class of materials.